2008
DOI: 10.1038/mp.2008.26
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate as a spectroscopic marker of hippocampal structural plasticity is elevated in long-term euthymic bipolar patients on chronic lithium therapy and correlates inversely with diurnal cortisol

Abstract: While an excess of glucocorticoids is associated with hippocampal pathology in mood disorders, lithium exerts robust neuroprotective and neurotrophic effects. Here, 21 stably remitted bipolar I patients who had been on chronic lithium maintenance therapy, on average, for more than a decade, and 19 carefully matched healthy controls were studied using 3 T 1 Hmagnetic resonance spectroscopy of left and right hippocampus. Salivary cortisol samples were obtained to assess activity of the hypothalamus-pituitary-adr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
3
12

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 82 publications
2
62
3
12
Order By: Relevance
“…These findings are in keeping with those of previous crosssectional studies, which reported greater brain NAA levels in Li-treated patients with bipolar disorder versus those without current Li treatment 13,14 or comparable brain NAA levels between Li-treated patients and controls. [15][16][17] Contrary to our findings, a single study in patients with shorter duration of illness showed no differences in brain NAA levels between Li-treated and untreated patients. 15 Two additional studies reported greater brain NAA levels among Li-treated patients than controls.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…These findings are in keeping with those of previous crosssectional studies, which reported greater brain NAA levels in Li-treated patients with bipolar disorder versus those without current Li treatment 13,14 or comparable brain NAA levels between Li-treated patients and controls. [15][16][17] Contrary to our findings, a single study in patients with shorter duration of illness showed no differences in brain NAA levels between Li-treated and untreated patients. 15 Two additional studies reported greater brain NAA levels among Li-treated patients than controls.…”
Section: Discussioncontrasting
confidence: 55%
“…[8][9][10][11] A single prospective study reported a small NAA increase after 4 weeks of Li treatment, 3 whereas another investigation found an NAA decrease after 6 weeks of Li exposure. 12 Cross-sectional studies have also been inconsistent, with reports of greater 13,14 as well as comparable [15][16][17] brain NAA levels in Li-treated versus control participants.…”
Section: Introductionmentioning
confidence: 99%
“…Four other studies reported results for glutamate, but not for the combined Glx signal. Two of these reported elevated glutamate in bipolar patients (Colla et al 2009;Lan et al 2009). One additional study examined Glx in older adolescents and young adults (mean age = 22) and found elevated Glx in the bipolar patients (Cecil et al 2002).…”
Section: Glutamate and Glutaminementioning
confidence: 95%
“…153 There has been little consistency in the results of studies to date examining other neurochemicals with proton MRS. Interestingly, in a recent study of 21 stable remitted patients with BD taking lithium, patients were found to have increased hippocampal glutamate, which correlated strongly with NAA concentrations. 134 There was also a negative correlation between hippocampal glutamate and diurnal cortisol, and the authors suggest that the high glutamate levels may be related to chronic lithium maintenance, which acts to protect the hippocampus from adverse effects of stress and glucocorticoids. 134 Phosphorus MRS Increased levels of phosphomonoesters (PMEs) imply an increased rate of membrane phospholipid turnover, whereas decreased PME levels indicate a stalling of membrane synthesis.…”
Section: Proton Mrsmentioning
confidence: 99%
“…134 There was also a negative correlation between hippocampal glutamate and diurnal cortisol, and the authors suggest that the high glutamate levels may be related to chronic lithium maintenance, which acts to protect the hippocampus from adverse effects of stress and glucocorticoids. 134 Phosphorus MRS Increased levels of phosphomonoesters (PMEs) imply an increased rate of membrane phospholipid turnover, whereas decreased PME levels indicate a stalling of membrane synthesis. Interestingly, PME appears to be increased in both the depressed and manic phases of BD, 135 but reduced in frontal and temporal regions during the euthymic phase compared with healthy controls.…”
Section: Proton Mrsmentioning
confidence: 99%